Isoquercetin as an Adjunct Therapy in Patients With Kidney Cancer Receiving First-Line Sunitinib (QUASAR): Results of a Phase I Trial - Buonerba, Carlo; De Placido, Pietro; Bruzzese, Dario; Pagliuca, Martina; Ungaro, Paola; Bosso, Davide; Ribera, Dario; Iaccarino, Simona; Scafuri, Luca; Liotti, Antonietta; Romeo, Valeria; Izzo, Michela; et al. (Frontiers in Pharmacology, 2018)
Sunitinib is the most commonly prescribed drug for advanced renal cell carcinoma in the first-line setting and has been associated with multiple adverse events related to its on- and off- target effects, including hand and foot syndrome and fatigue. It was hypothesized that sunitinib-induced fatigue may be related to off target inhibition of the AMPK enzyme, which results in impairment of energy-producing processes at a systemic level. Quercetin is a naturally occurring flavonol with established AMPK-stimulating activity. While clinical use of quercetin is limited by its poor bio-availability, quercetin-3-O-β-d-glucopyranoside, that is isoquercetin, has an improved pharmacokinetic profile. On the grounds of the in vitro stimulatory activity with respect to AMPk, we hypothesized that oral isoquercetin could improve fatigue in kidney cancer patients receiving sunitinib. Given the lack of data on the safety of isoquercetin given concomitantly with sunitinib, we conducted a phase I trial to assess the safety of GMP manufactured isoquercetin given at two dose levels (450 mg and 900 mg a day). In the 12-patient study cohort included in this study, isoquercetin was administered concomitantly with 50 mg sunitinib for a median 81 days (IQR, 75,5, 86,5). None of the 12 patients required isoquercetin suspension or isoquercetin dose reduction because of adverse events. No abnormalities in ECG, heart or lower limbs doppler ultrasound were detected. A statistically significant improvement was reported for the FACIT fatigue score (6.8 points; 95% CI: 2.8 to 10.8; p=0.002) and for the FACIT Adverse Events score (18.9 points; 95% CI:9.1 to 28.8; p<0.001) after isoquercetin consumption vs. baseline. In this phase I trial, isoquercetin was remarkably safe, with a preliminary signal of activity in terms of improvement of sunitinib adverse events.